Going Under: The Metro and the Search for Oneself in Julio Cortázar's "The Pursuer" - Patricia E. Reagan (Studies in 20th & 21st Century Literature, 2006)
Johnny's metaphysical experience on the metro in Julio Cortázar's "The Pursuer" catalyzes his perception. The metro incident and the ensuing commentary propel all the elements of the narrative. The metro facilitates the development of Johnny's character; relates his character to Charlie Parker; aids our comprehension of the relationship between the metro and Johnny's music; and establishes the metaphysical difference between Johnny and Bruno. The subway is also physical space in which Cortázar reveals a view of time perception in which chronological time succumbs to subjective time. Johnny's metacognitive search for the yonder marks a change in Cortázar's narrative preoccupations and anticipates Rayuela in both technique and content. The function of the metro in "The Pursuer" is related to travel in literature as well as in other Cortázar stories. The underground journey represented by the metro prompts the reader to join Cortázar's difficult search for heightened perception which begins below the surface. This search leads him to the postulation that art can open doors that lead to the más allá.
Keywords: Julio Cortázar; The Pursuer; metaphysical; time; perception; más allá